2020
DOI: 10.3390/biom11010043
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Bioinspired Formation of Inorganic Oxides: Structural Evidence of the Electrostatic Nature of the Interaction between a Mononuclear Inorganic Precursor and Lysozyme

Abstract: Nature has evolved several molecular machineries to promote the formation at physiological conditions of inorganic materials, which would otherwise be formed in extreme conditions. The molecular determinants of this process have been established over the last decade, identifying a strong role of electrostatics in the first steps of the precipitation. However, no conclusive, structure-based evidence has been provided so far. In this manuscript, we test the binding of lysozyme with silica and titania potential p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“… 12 However, no such interaction could be observed for silicic acid. 12 A recent study suggests that liquid–liquid phase separation (LLPS) is responsible for driving the polymerization; however, the LLPS is related to overall charge, 13 and there are reports that lysozyme tends not to undergo LLPS at pH values around 7. 14 It has been previously demonstrated that lysozyme catalyzes the silica colloid formation from silicon alkoxide solutions and dilute water glass solutions around neutral pH.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“… 12 However, no such interaction could be observed for silicic acid. 12 A recent study suggests that liquid–liquid phase separation (LLPS) is responsible for driving the polymerization; however, the LLPS is related to overall charge, 13 and there are reports that lysozyme tends not to undergo LLPS at pH values around 7. 14 It has been previously demonstrated that lysozyme catalyzes the silica colloid formation from silicon alkoxide solutions and dilute water glass solutions around neutral pH.…”
Section: Introductionmentioning
confidence: 98%
“… 17 However, no evidence of structural distortion has been observed by solution nuclear magnetic resonance (NMR) spectroscopy. 12 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations